Aquaculture and COVID-19: impacts on the production of tilapia in the central zone of the State of Hidalgo, Mexico. - Acosta-Pérez, Víctor Johan; Salinas Martínez, Jesus Armando; Vega Sánchez , Vicente; Zepeda Velázquez , Andrea Paloma; Reyes Rodríguez , Nydia Edith; Gómez De Anda, Fabián Ricardo; de la Rosa Arana, Jorge Luis; López Rivera , Maria Isabel (Agricultura, Sociedad y Desarrollo, 2025)
The pandemic (COVID-19) caused by the SARSCov-2 virus was a highly important event, with adverse effects in the economies of many countries, mainly developing countries; the event affected most industries, including those in the agriculture and livestock sector. In Mexico, aquaculture is considered a farming activity of recent development, with an important economic potential in some zones of the country; however, its development could have been affected by the COVID-19 pandemic. Because of this, information was gathered through semi-structured interviews to evaluate the effects of COVID-19 in small-scale tilapia producers in Valle del Mezquital, Hidalgo, Mexico. This evaluation evidenced a loss of employment of 23.53%, in addition to 67.41% of the farms, mentioning that their business had losses with a maximum value of 10,335.13 USD in one year of farming. The reductions were associated mainly with discrepancies in sales (35.29%) and the loss of commercialization channels (41.17%). However, the farms mentioned that the economic recovery of their businesses could be supported by actions such as the application of added value to the product (52.94%) and financial backing in the acquisition of fry (35.29%). The effects identified from COVID-19 in tilapia aquaculture showed trends that could be useful in the development of strategies for mitigation and recuperation of this industry.